2014
DOI: 10.4238/2014.september.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Torasemide reduces dilated cardiomyopathy, complication of arrhythmia, and progression to heart failure

Abstract: ABSTRACT. The aim of this study was to analyze the incidence and types of arrhythmia and their relationship with the severity and prognosis of chronic heart failure (CHF) in patients with dilated cardiomyopathy (DCM), and to investigate the therapeutic effect of torasemide versus furosemide on CHF and incidence of arrhythmia. DCM patients with NYHA cardiac function II-IV were continuously monitored using a 24-h dynamic electrocardiogram (Holter), and arrhythmia incidence was analyzed by computer automatic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…This finding may be explained by the reported ability of torasemide to reduce trans-cardiac extraction of circulating aldosterone [47] and/or by the direct inhibition of aldosterone synthase activity. The data are in agreement with previous studies reporting that torasemide is not an MR antagonist [41] but reduces the expression of aldosterone synthase and fibrosis in the left ventricles of rats with dilated cardiomyopathy [35,48] as well as the incidence of atrial fibrillation in patients with dilated cardiomyopathy [49]. Importantly and consistently, the regulation e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This finding may be explained by the reported ability of torasemide to reduce trans-cardiac extraction of circulating aldosterone [47] and/or by the direct inhibition of aldosterone synthase activity. The data are in agreement with previous studies reporting that torasemide is not an MR antagonist [41] but reduces the expression of aldosterone synthase and fibrosis in the left ventricles of rats with dilated cardiomyopathy [35,48] as well as the incidence of atrial fibrillation in patients with dilated cardiomyopathy [49]. Importantly and consistently, the regulation e.g.…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed that part of this mortality and morbidity benefit over furosemide might be related to the above‐mentioned pharmacokinetic differences and also to the pharmacodynamic properties of torasemide. Although not demonstrated in the dog, beyond its action on the thick loop of Henle, torasemide exerts vasodilating and antialdosterone effects, which are both beneficial in hypervolemic states . In vitro and in vivo studies have suggested that torasemide has antialdosterone properties, either by blocking the mineralocorticoid receptor binding of aldosterone (although recent data suggested that torasemide does not act as a mineralocorticoid receptor antagonist) or by inhibition of aldosterone synthase, with these effects being associated with prevention of atrial fibrosis and atrial fibrillation in mice as well as improvement of cardiac function and survival rate in rats with CHF .…”
Section: Discussionmentioning
confidence: 99%
“…Although not demonstrated in the dog, beyond its action on the thick loop of Henle, torasemide exerts vasodilating and antialdosterone effects, which are both beneficial in hypervolemic states. [33][34][35][36][37][38][39][40][41][42][43][44][45][46] In vitro and in vivo studies have suggested that torasemide has antialdosterone properties, either by blocking the mineralocorticoid receptor binding of aldosterone 43 (although recent data suggested that torasemide does not act as a mineralocorticoid receptor antagonist) 66 or by inhibition of aldosterone synthase, with these effects being associated with prevention of atrial fibrosis and atrial fibrillation in mice as well as improvement of cardiac function and survival rate in rats with CHF. 42,44,45 Whether or not the mechanism underlying the risk reduction of reaching the composite cardiac endpoint observed in the Torasemide group of the present trial is related to an antialdosterone effect remains to be determined by further studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations